MicroRNA-203 impacts on the growth, aggressiveness and prognosis of hepatocellular carcinoma by targeting MAT2A and MAT2B genes - Simile, Maria M. (Oncotarget, 2019)
Hepatocellular carcinoma (HCC) is characterized by the down-regulation of the liver-specific methyladenosyltransferase 1A (MAT1A) gene, encoding the S-adenosylmethionine synthesizing isozymes MATI/III, and the up-regulation of the widely expressed methyladenosyltransferase 2A (MAT2A), encoding MATII isozyme, and methyladenosyltransferase 2B (MAT2B), encoding a β-subunit without catalytic action that regulates MATII enzymatic activity. Different observations showed hepatocarcinogenesis inhibition by miR-203. We found that miR-203 expression in HCCs is inversely correlated with HCC proliferation and aggressiveness markers, and with MAT2A and MAT2B levels. MiR-203 transfection in HepG2 and Huh7 liver cancer cells targeted the 3’-UTR of MAT2A and MAT2B, inhibiting MAT2A and MAT2B mRNA levels and MATα2 and MATβ2 protein expression. These molecular events were paralleled by an increase in SAM content and were associated with growth restraint and apoptosis, inhibition of cell migration and invasiveness, and suppression of the expression of CD133 and LIN28B stemness markers. In contrast, MAT2B transfection in the same cell lines led to a rise of both MATβ2 and MATα2 expression, associated with increases in cell growth, migration, invasion and overexpression of stemness markers and p-AKT. Altogether, our results indicate that the miR-203 oncosuppressor activity may at least partially depend on its inhibition of MAT2A and MAT2B and show, for the first time, an oncogenic activity of MAT2B linked to AKT activation.